Literature Review on Key Macroeconomic Issues 2018 to 2025 - Khoirul Anam; Syamsul Arifin; Devangga Putra Adhitya Pratama; Mahmud Ismail (CV Pena Jaya Pers, 2025)
The period from 2018 to 2025 has been marked by profound macroeconomic turbulence and transformation, shaped by the COVID-19 pandemic, geopolitical tensions, climate shocks, and rapid technological change. This literature review synthesizes scholarly and institutional research on the evolution of key macroeconomic indicators, such as inflation, unemployment, GDP growth, fiscal and monetary policy, global trade, and post-pandemic recovery, while integrating cross-cutting themes of compensation, environmental factors, and job satisfaction. Drawing on data from the World Bank, IMF, UNCTAD, ILO, and recent peer-reviewed studies, the review highlights the interplay between policy responses and macroeconomic outcomes, the shifting dynamics of global trade and finance, and the persistent challenges of inequality, debt, and climate risk. Special attention is given to country case studies (United States, Euro Area, China, Indonesia) and to the methodological advances in macroeconomic research during this period. The findings reveal that while the global economy demonstrated resilience in the face of unprecedented shocks, recovery has been uneven and fragile, with developing economies bearing disproportionate burdens. Inflation surged to multi-decade highs before moderating, labor markets experienced both acute disruptions and rapid rebounds, and fiscal and monetary authorities deployed extraordinary measures, often in coordination, to stabilize economies. Yet, the legacy of heightened debt, persistent inequality, and climate vulnerability underscores the need for integrated, forward-looking policy frameworks. The review concludes by identifying gaps in the literature and proposing avenues for future research, particularly in the integration of environmental and social dimensions into macroeconomic analysis.